Endoplasmic reticulum oxidoreductin 1α as a potential therapeutic target in diseases: from oxidative protein folding to pathophysiological mechanisms - He, Fang; Ge, Xiaoyue; Liu, Xiaohui (Frontiers in Pharmacology, 2025)
Endoplasmic reticulum oxidoreductin 1α (ERO1α), an ER-resident thiol oxidoreductase, has been implicated in disulfide bond formation during protein folding by acting as an electron acceptor transfer for protein disulfide isomerase (PDI). This process reduces oxygen to H2O2 contributing up to 25% of the induced cellular reactive oxygen (ROS). However, research has shown that disulfide bond formation in certain proteins is preferentially catalyzed directly by ERO1, rather than indirectly through PDI. ERO1α also contributes to calcium homeostasis and endoplasmic reticulum stress (ERS). Disruption of these processes is closely associated with a variety of diseases, while the detailed molecular and cellular mechanisms underlying these processes remain to be elucidated. In mammals, tissue-specific ERO1α knockout and inhibitors have been developed to elucidate the cell-specific functions, but ERO1α inhibitors are not specific and may have significant cytotoxicity. This reviews provide an in depth summary regarding ERO1α in various disease processes, including cardiovascular diseases, diabetes, and cancer. Furthermore, it highlights the potential of ERO1α as a potential biomarker and a novel therapeutic target in clinical diseases.